RESPONSIBILITAS HUKUM ISLAM DALAM MENGHADAPI TANTANGAN GLOBALISASI - Abd. Jabar Abdul (IAIN Ambon, 2017)
Islamic law aims to materialize the welfare and happiness of mankind. Habituation of Islamic law which originated from revelations of Allah and sunnah of Prophet, requires a comprehensive understanding to the purpose of Allah in establishing Islamic law to mankind. The awareness on this case has implication that welfare and happiness of human are laid in how long implemented the Islamic law. A mankind comprehension and consistency to Islamic law in early period has freed human from the bondage of idolatry and oppression, spirit and jihad enthusiasm are emitted from Islamic law has led to the glory and resurrection of Islamic civilization. Conversely, the setback and lag of Muslims civilization were originated from negligence, denial and weakening of Muslim jihad enthusiasm. Encountering the modernization and globalization challenges, there is no choice but returning to the spirit of Islamic law that can provide inspiration for strengthening a human integrity based on monotheism, development of scientific ethos, good deeds, and reformation movement suggested that Islamic law is always dynamic, universal and responsive to dynamics of the progress of time. Keywords: responsibility, benefit , Islamic law